2011
DOI: 10.4081/reumatismo.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular therapy with infliximab in psoriatic arthritis: efficacy and safety in refractory monoarthritis

Abstract: Objective: To evaluate efficacy and safety of intra-articular therapy (IA) with infliximab (IFX), in patients with psoriatic arthritis (PsA) and refractory monoarthritis. Methods: Four male and 1 female aged from 25 to 71 years and disease duration from 1 to 25 years, affected by PsA (CASPAR criteria) were observed . All patients were treated with immunomodulators (methotrexate, leflunomide, cyclosporin A), 3/5 with concomitant steroids, 4/5 with NSAID’s. Only 1 patient were treated with IFX 5 mg/kg IV every 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…50 Several studies concerning the use of intra-articular anti-TNFα agents have been published so far but results are not conclusive, with a wide range of clinical response and differences in the study design. 1122…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Several studies concerning the use of intra-articular anti-TNFα agents have been published so far but results are not conclusive, with a wide range of clinical response and differences in the study design. 1122…”
Section: Discussionmentioning
confidence: 99%
“…However only conflicting results are available in literature. [11][12][13][14][15][16][17][18][19][20][21][22] At present, both magnetic resonance imaging (MRI) and ultrasonography (US) are established methods to evaluate the severity of monoarthtitis flares in these conditions; [23][24][25][26] furthermore, US improves the performance of intra-articular injections overcoming technical problems such as the correct position of the needle and the aspiration of joint effusion. 27 In fact it is well know that only in 50% of intra-articular injections is the drug placed in the right place and this strongly decreases the efficacy of these procedures.…”
Section: Introductionmentioning
confidence: 99%
“…22 There have also been scattered reports of IA delivery of TNFi to treat inflammatory arthritic conditions, including JIA. For example, Bello et al 26 reported on 5 adults with psoriatic arthritis who responded to IA infliximab, and Conti et al 27 reported good responses in 9 of 10 subjects with rheumatoid or psoriatic arthritis receiving IA infliximab. Unlike IACS, the TNFi were not designed for depot injections; indeed, improvements in systemic symptoms and inflammatory markers have also been observed with local TNFi injections.…”
Section: Therapy Of Jiamentioning
confidence: 97%
“…Unlike IACS, the TNFi were not designed for depot injections; indeed, improvements in systemic symptoms and inflammatory markers have also been observed with local TNFi injections. 26,28 The comparative effectiveness of IA TNFi versus IACS is unclear. A RCT comparing IA etanercept to IA betamethasone showed etanercept to be superior, 29 while a comparison of IA etanercept and IA methylprednisolone showed equivalence.…”
Section: Therapy Of Jiamentioning
confidence: 99%